EXPERIMENTAL INVESTIGATION OF EPOXY/POLY(AMINO AMIDE)/PHTHALIC ANHYDRIDE: MECHANICAL PROPERTIES AND THERMAL STABILITY - Eduart Wolok, Fahriadi Pakaya (International Journal of Advanced Science and Technology, 2020)
Epoxy resin is one of materials engineering that is widely applied especially in the shipping industry, aviation, automotive, and others. With a variety of applications led many scientists in the field of materials engineering work to improve the properties and ability of the epoxy either by changing the structure of epoxy. One way to improve the properties of epoxy is adding certain compounds that can react and able to change the properties of the epoxy according to the requirement. In this study, to improve the properties of the epoxy, then added phthalic anhydride compounds. The epoxy was cured using poly(amino amide) (PAA) as hardener at 40 wt%. The composition of phthalic anhydride (PA) was added at 5, 10, 15 and 20 wt%. The epoxy/PAA/PA was evaluated as the effect of phthalic anhydride composition. The addition of phthalic anhydride increase the elongation at break, energy and impact strength but decreased tensile strength and thermal stability. The optimum of energy and impact strength was at 20wt% phthalic anhydride respectively 0.398 J and 5450,48 J/m2. The addition of phthalic anhydride decrease the thermal properties of epoxy / PAA / PA. Stability of the lowest in the addition of 15wt% PA around 146oC.